Encyclopedia of Irkutsk architects - Tkacheva, Marina (project baikal, 2025)
The article gives a review of the book “Irkutsk Architects” prepared on the basis of the articles published in Project Baikal journal within 20 years of its work and several studies by the INRTU professorship. The structure of the book and its individual sections are characterized